2021
DOI: 10.21037/apm-20-2194
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with advanced colorectal cancer: a predictive nomogram including BMI, sex and age

Abstract: Background: Health-related quality of life (HRQoL) is not universally assessed in metastatic colorectal cancer (mCRC) patients. We tried to identify patient subgroups for whom HRQoL assessment should be strongly encouraged.Methods: Consecutive mCRC patients who had been deemed candidates for first-line chemotherapy were enrolled in a prospective study (NCT03873064) and asked to complete the HRQoL questionnaire EORTC QLQ-C30. Primary endpoint was the Global Health Status (GHS) of EORTC QLQ-C30. A nomogram was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, Formica et al. reported that BMI was strongly associated with the quality of life of colorectal cancer patients, where BMI < 23 kg/m 2 was associated with a poor score of health-related quality of life (HRQoL) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Formica et al. reported that BMI was strongly associated with the quality of life of colorectal cancer patients, where BMI < 23 kg/m 2 was associated with a poor score of health-related quality of life (HRQoL) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It might be challenging to employ the prediction models in clinical practice since it was not easy for doctors to collect so many variables. Formica et al [37] proposed a nomogram to predict health-related quality of life among colorectal cancer patients, and the nomogram included only age, sex, and body mass index, but the C-statistics of the nomogram was only 0.67, indicating that its predictive power was not very strong. The C-statistics for the prediction nomogram put forth in this study could reach 0.90 in the training set and 0.85 in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of precision medicine has increased the advantages of nomograms and created greater space for their application. Nomograms for predicting anastomotic fistula, liver metastasis, and survival after rectal cancer surgery have been reported ( 16 20 ). However, there are few studies assessing nomograms for preoperative prediction of EMVI in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%